PENGARUH TOTAL ARUS KAS, DEBT TO EQUITY RATIO, UKURAN PERUSAHAAN DAN LABA AKUNTANSI TERHADAP RETURN SAHAM PADA SEKTOR MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA - Pretty; Robby Handoko; Dicky; Adam Afiezan (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2020)
This study aims to determine and analyze the effect of Total Cash Flow, Debt toEquity Ratio, Firm Size and Accounting Income on Stock jReturns in the Food andBeverage Sector on the Indonesia Stock Exchange. The research approach used isaquantitative japproach. The jsampling method jwas purposive sampling, a sampleof 13 companies in the jfood jand jbeverage sector listed on the Indonesian stockjexchange multiplied by 4 years in the study period. The results showed that totalcash flow, debt to equity ratio, firm size and profit had no effect and were notsimultaneously significant on stock returns in the food and beverage sector on theIndonesian stock exchange. with the test results obtained the calculated F value(0.182) < F table (2.57) and a significance of 0.94 > 0.05. Total cash flow has noeffect and is not partially significant on stock returns in the food and beveragesector on the Indonesian stock exchange, with the test results obtained that thetcount is -0.52 with a significant value of 0.606 while the ttable is 2.011 with asignificant 0.05. Debt to equity ratio has no effect and is not partially significant onstock returns in the food and beverage sector on the Indonesian stock exchange withthe test results obtained that the tcount is 0.123 with a significant value of 0.903while the ttable is 2.011 with a significant 0.05. Firm size has no effect and is notpartially significant on stock returns in the food and beverage sector on theIndonesian stock exchange with the test results obtained that the tcount is -0.264with a significant value of 0.793 while the ttable is 2.011 with a significant 0.05.Accounting income has no effect and is not partially significant on stock returns inthe food and beverage sector on the Indonesian stock exchange with the test resultsobtained that the tcount is 0.356 with a significant value of 0.723 while the ttable is2.011 with a significant 0.05. With the results of testing the value of R Square (R2)the coefficient of determination is 0.015 or equal to 1.5%. This means that 1.5% ofstock returns can be explained by changes in independent variables and theremaining98.5%is influenced by other variables not examined in this study